Analysis of the start-up and variable load operation of a combined cycle power plant for off-grid mines. (2017) - Romero, Alberto; Chacartegui, Ricardo; Becerra, José Antonio; Carvalho, Monica; Millar, Dean L.
Mining is an economic activity that intensively uses energy in the extraction and processing of raw minerals. This means that large amounts of greenhouse gas (GHG) emissions are released into the atmosphere. Natural gas in conjunction with combined cycle power plants (CCPP) could replace other more contaminant sources of energy, such as diesel, which is the fuel traditionally preferred in mining to generate power in remote sites. Today, however, the operation of CCPP in stand-alone power systems under frequent load variations and plant start-ups remains challenging. During start-up operations of CCPP, high thermal and mechanical stresses negatively affect the components of the heat recovery steam generator (HRSG). Special off-grid CCPP applications require additional considerations regarding design and operation. Motivated by the challenges associated with using CCPPs in off-grid mines as a main source of electrical power, a CCPP mathematical model was developed to evaluate load changes during start-up and shut-down operations. Two strategies were investigated to minimise consumption of steam: bypass of gas turbine (GT) exhaust gases during a time interval and GT warm-up hold. Results demonstrated that these strategies reduced stresses on the steam drum and lifetime consumption, but could also induce additional fatigue cycles during start-up operations.